Growth and scintillation properties of Ce doped Gd2Si2O7/SiO2 eutectics. (May 2015) - Kamada, Kei; Kurosawa, Shunsuke; Murakami, Rikito; Yokota, Yuui; Pejchal, Jan; Ohashi, Yuji; Yoshikawa, Akira
Abstract: Ce:Gd2 Si2 O7 /SiO2 eutectic was grown by the μ-PD method. The square-shape sample with a side of 5 mm and a length of 15 mm was obtained. Two phases of orthorhombic Gd2 Si2 O7 and SiO2 was observed. Rod-phase was SiO2 and matrix phase was Gd2 Si2 O7 . Ce 3+ 4f5d emission have been observed at 400nm. The sample showed light yield of around 16, 000 photons/MeV. Scintillation decay time was 46.3ns(21%) 249ns(79%).